Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine whether each number is a solution of the inequality [tex]\( 2x + 4 \geq -1 \)[/tex], we need to substitute each number into the inequality and verify if the inequality holds true.
### Part (a): Checking if [tex]\( 3 \)[/tex] is a solution.
1. Substitute [tex]\( 3 \)[/tex] for [tex]\( x \)[/tex] in the inequality:
[tex]\[ 2(3) + 4 \geq -1 \][/tex]
2. Simplify the expression:
[tex]\[ 6 + 4 \geq -1 \][/tex]
[tex]\[ 10 \geq -1 \][/tex]
Since [tex]\( 10 \geq -1 \)[/tex] is a true statement, [tex]\( 3 \)[/tex] is a solution to the inequality.
- Answer: Yes
### Part (b): Checking if [tex]\( -1 \)[/tex] is a solution.
1. Substitute [tex]\( -1 \)[/tex] for [tex]\( x \)[/tex] in the inequality:
[tex]\[ 2(-1) + 4 \geq -1 \][/tex]
2. Simplify the expression:
[tex]\[ -2 + 4 \geq -1 \][/tex]
[tex]\[ 2 \geq -1 \][/tex]
Since [tex]\( 2 \geq -1 \)[/tex] is a true statement, [tex]\( -1 \)[/tex] is a solution to the inequality.
- Answer: Yes
### Part (c): Checking if [tex]\( 1 \)[/tex] is a solution.
1. Substitute [tex]\( 1 \)[/tex] for [tex]\( x \)[/tex] in the inequality:
[tex]\[ 2(1) + 4 \geq -1 \][/tex]
2. Simplify the expression:
[tex]\[ 2 + 4 \geq -1 \][/tex]
[tex]\[ 6 \geq -1 \][/tex]
Since [tex]\( 6 \geq -1 \)[/tex] is a true statement, [tex]\( 1 \)[/tex] is a solution to the inequality.
- Answer: Yes
In conclusion:
- [tex]\( 3 \)[/tex] is a solution to the inequality.
- [tex]\( -1 \)[/tex] is a solution to the inequality.
- [tex]\( 1 \)[/tex] is a solution to the inequality.
### Part (a): Checking if [tex]\( 3 \)[/tex] is a solution.
1. Substitute [tex]\( 3 \)[/tex] for [tex]\( x \)[/tex] in the inequality:
[tex]\[ 2(3) + 4 \geq -1 \][/tex]
2. Simplify the expression:
[tex]\[ 6 + 4 \geq -1 \][/tex]
[tex]\[ 10 \geq -1 \][/tex]
Since [tex]\( 10 \geq -1 \)[/tex] is a true statement, [tex]\( 3 \)[/tex] is a solution to the inequality.
- Answer: Yes
### Part (b): Checking if [tex]\( -1 \)[/tex] is a solution.
1. Substitute [tex]\( -1 \)[/tex] for [tex]\( x \)[/tex] in the inequality:
[tex]\[ 2(-1) + 4 \geq -1 \][/tex]
2. Simplify the expression:
[tex]\[ -2 + 4 \geq -1 \][/tex]
[tex]\[ 2 \geq -1 \][/tex]
Since [tex]\( 2 \geq -1 \)[/tex] is a true statement, [tex]\( -1 \)[/tex] is a solution to the inequality.
- Answer: Yes
### Part (c): Checking if [tex]\( 1 \)[/tex] is a solution.
1. Substitute [tex]\( 1 \)[/tex] for [tex]\( x \)[/tex] in the inequality:
[tex]\[ 2(1) + 4 \geq -1 \][/tex]
2. Simplify the expression:
[tex]\[ 2 + 4 \geq -1 \][/tex]
[tex]\[ 6 \geq -1 \][/tex]
Since [tex]\( 6 \geq -1 \)[/tex] is a true statement, [tex]\( 1 \)[/tex] is a solution to the inequality.
- Answer: Yes
In conclusion:
- [tex]\( 3 \)[/tex] is a solution to the inequality.
- [tex]\( -1 \)[/tex] is a solution to the inequality.
- [tex]\( 1 \)[/tex] is a solution to the inequality.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.